A Innovation in Learning Elements Of Language (Vocabulary) Using Eclectical Methods: Sebuah Inovasi Pembelajaran Unsur Bahasa (Vocabulary) Menggunakan Metode Eklektik - Wahyu Retno Ningsih (LPPM Institut Studi Islam Sunan Doe, 2023)
This study aims to determine the techniques used in learning language elements using eclectic methods, innovations in learning Arabic, and innovative Arabic learning principles. This research was conducted with a qualitative descriptive method. Data collection techniques were carried out using literature studies and guided group discussions while data analysis techniques used the Miles & Huberman interactive analysis model. The results of this study, firstly, explain the techniques used in learning language elements using the eclectic method which ensures that this eclectic method is rich in techniques as a result of a collection of selected and collaborated methods of technique. Second, innovation in learning should have a teaching style and art, so students don't feel bored in participating in the learning process. Third, the principle of language learning which has several systems, integrated, separate, and combined and has several principles, namely, the principle of priority, the principle of accuracy, the principle of gradation, the principle of motivation, and the principle of validation.